2018
DOI: 10.1111/ffe.12775
|View full text |Cite|
|
Sign up to set email alerts
|

Ratcheting in pressurized pipes and equipment: A review on affecting parameters, modelling, safety codes, and challenges

Abstract: The current study has attempted to comprehensively review ratcheting response of materials involving various influential parameters such as loading spectra, thermal cycles, stress levels, stress raisers, strain rate, and visco‐plasticity and material types with a focus on pressurized pipes and equipment. The mechanism of deformation, types, and the rate of progress over stages of ratcheting were discussed. Safety design codes and procedures were highlighted for reliable design of pressurized pipes against prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 246 publications
(501 reference statements)
0
21
0
Order By: Relevance
“…Ahmadzadeh and Varvani developed a kinematic hardening rule by introducing an internal variable, trueb¯, into the dynamic recovery term to control the evolution of backstress increments over loading process. The dynamic recovery in the A‐V model was formulated through involvement of ()trueα¯normalδtrueb¯ to enable evolution of yield surface on the deviatoric stress space accumulating for the ratcheting strain with a gradual decreasing rate. The framework of the hardening rule consisted of relatively less number of coefficients empowering the model to assess ratcheting with less CPU/computation time.…”
Section: Analysis Of Ratcheting and Stress Relaxation At Notch Rootmentioning
confidence: 99%
“…Ahmadzadeh and Varvani developed a kinematic hardening rule by introducing an internal variable, trueb¯, into the dynamic recovery term to control the evolution of backstress increments over loading process. The dynamic recovery in the A‐V model was formulated through involvement of ()trueα¯normalδtrueb¯ to enable evolution of yield surface on the deviatoric stress space accumulating for the ratcheting strain with a gradual decreasing rate. The framework of the hardening rule consisted of relatively less number of coefficients empowering the model to assess ratcheting with less CPU/computation time.…”
Section: Analysis Of Ratcheting and Stress Relaxation At Notch Rootmentioning
confidence: 99%
“…Interactions between thermal gradient and cyclic thermal load create thermal ratcheting deformation . Therefore, ratcheting is an important concern for pressure component design . Design rules limiting inelastic strain have been established, such as ASME B&PV Code, RCC, and R5 .…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of ratcheting severely influences the fatigue life of engineering components, especially for structures subjected to low cycle fatigue . Experimental studies on cyclic‐plastic behaviour of ferrous and non‐ferrous materials by numerous investigators have revealed the influence of mean stress, stress amplitude, and nature of loading on ratcheting behaviour of materials, and there exists several reports on modelling the cyclic‐plastic behaviour of materials. The existing constitutive models are popularly focused towards predicting the ratcheting behaviour of ferrous materials.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation of the shakedown phenomenon considering combined hardening models typically demands the use of linear hardening rule in the KH component . But the earlier investigators have dealt with this problem by incorporating a small amount of nonlinearity in the third backstress of the KH component in the original Chaboche model to achieve simulations for the stabilized rate of ratcheting.…”
Section: Introductionmentioning
confidence: 99%